The Elephant and the Sea - Vere, Ed (New York : Doubleday Books for Young Readers, 2024)
"Gabriel the elephant reminisces on his younger days and his dreams of being a member of a brave lifeboat crew."-- Provided by publisher.
Ages 3-7.
Keywords: Elephants -- Juvenile fiction; Lifeboats -- Juvenile fiction; Rescue work -- Juvenile fiction; Elephants -- Fiction; Lifeboats -- Fiction; Rescue work -- Fiction; Animal fiction; Picture books